Fatigue surface crack growth in cylindrical specimen under combined loading - Citarella, R.; Lepore, M.; Shlyannikov, V.; Yarullin, R. (Engineering fracture mechanics, 2014)
•There is a strong experimental effort to validate the numerical procedure.•The proposed procedure predict residual fatigue life under mixed mode conditions.•A comparison is provided between different criteria for crack path assessment. The subject for studies is a steel bar of circular cross-section with straight-fronted edge notch undergoing fatigue loads. Both the optical microscope measurements and the crack opening displacement (COD) method are used to monitor and investigate both crack depth and crack length during the tests. The variation of crack growth behavior is studied under cyclic axial and combined tension+torsion fatigue loading. Results show that cyclic Mode III loading superimposed on the cyclic Mode I leads to a fatigue life reduction. In parallel to the experimental activity, numerical calculations are performed based on three-dimensional DBEM analysis to determine the stress intensity factors along curvilinear surface crack front and fatigue life prediction. The experimental fatigue crack growth results obtained from round bar specimens have been compared with the numerical predictions. The computational DBEM results are found to be in satisfactory agreement with the experimental findings.